Micromycetes on Pisum sativum var. arvense - Joanna Marcinkowska (Acta Mycologica, 2014)
Seeds of 11 Austrian winter pea genotypes, harvested at Radzików (CEP) in 1993 and 1994, were evaluated for fungi occurrence on Coon's agar medium in Petri plates. Number of species isolated depended on the genotype and year of collection. Alternaria alternata, Stemphylium botryosum were found on all the tested samples and Phoma pinodella and Fusarium poae were also common while Botrytis cinerea, Sclerotinia sclerotiorum and Mycosphaerella pinodes appeared to be common only in 1993. Three species occurred only once. The mycoflora was richer in 1993. The common seed inhabitants usually transmitted higher percentage of fungi than species occuring more seldom.